Doctoral Theses in Early Modern History: Recent Trends and Not-so-new Problems - Monteiro, Nuno (2019)
Based on the list of the theses defended in Portuguese universities in the last eight years, a brief assessment is made of the recent developments in the field of Early Modern History Studies in Portugal, highlighting its recent trends and persistent problems.